Experimental study of dielectric properties of composite materials pozzolan/DGEBA. Issue 2 (19th June 2015) - Irekti, Amar; Bezzazi, Boudjema; Smith, Agnès; Aribi, Chouaib
Abstract : The subject of composite materials with reinforced filler has been studied recently. This study to improve both the dielectric and structural characteristics of diglycidyl ether of bisphenol a (DGEBA) focused on the appropriate use (from 5% to 60 wt%) of pozzolan filler mechanically grinded to obtain a very fine particle size ( Ø  < 10 μm) and area surface of 23.5 m 2 g −1 . The dielectric properties were investigated at great filler concentrations by weight. Epoxy microcomposite samples with a good dispersion of nanoparticles in the epoxy matrix were prepared and experiments were performed to measure the capacitance ( C ), the electrical resistance ( R ), and impedance ( Z ) as a function of frequency (1 kHz–10 kHz). Measurements were made using dielectric spectroscopy over the temperature range 25–80°C. Using the scanning electron microscope (SEM), the morphologies and structure of the surface and fracture surfaces of Pozzolan/DGEBA composites were observed. POLYM. COMPOS., 38:324–331, 2017. © 2015 Society of Plastics Engineers